Valorization of castor oil-derived fatty acids for new bioactive compounds via chemo-enzymatic reactions: Valorization of castor oil-derived fatty acids for new bioactive compounds via chemo-enzymatic reactions - GANDHI BHUKYA; SHIVA SHANKER KAKI (Journal of Oilseeds Research, 2023)
Novel lipidic compounds were prepared from 10-Undecenoic (UDA) and 11-bromoundecanoic acids (BUA) which are well known castor derived fatty acids. Ten novel structured monoacylglycerol (MAG)-based phenolic lipids were prepared from 11-bromoundecanoic acid by chemo-enzymatic approach and 20 new triazole based UDA hybrids were synthesized by Click chemical synthesis. The synthesized compounds were characterized by spectra analysis and studied for their antioxidant, antimicrobial and cytotoxic activities.